2012
DOI: 10.1016/j.ijscr.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of all-terrain vehicle injuries in adults: A case series and review of the literature

Abstract: A paucity of research outside of North America is highlighted by this case series. Mandatory reporting of ATV related injury, educational, training and legislative measures are suggested as injury prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Failing to activate the ATV brakes limits the youth's ability to reduce the speed or to stop the vehicle, which likely prevents them from avoiding unexpected hazards, such as obstacles or bystanders (Fathallah et al, 2008). In fact, previous research has shown that a significant number of ATV incidents include hitting a stationary object (Balthrop et al, 2007;Concannon et al, 2012;Helmkamp et al, 2011;Jennissen, Wetjen, Hoogerwerf, O'Donnell, & Denning, 2018;Lower & Herde, 2012).…”
Section: Limitations Of Youthmentioning
confidence: 99%
“…Failing to activate the ATV brakes limits the youth's ability to reduce the speed or to stop the vehicle, which likely prevents them from avoiding unexpected hazards, such as obstacles or bystanders (Fathallah et al, 2008). In fact, previous research has shown that a significant number of ATV incidents include hitting a stationary object (Balthrop et al, 2007;Concannon et al, 2012;Helmkamp et al, 2011;Jennissen, Wetjen, Hoogerwerf, O'Donnell, & Denning, 2018;Lower & Herde, 2012).…”
Section: Limitations Of Youthmentioning
confidence: 99%
“…All-terrain vehicles riders were found to be significantly younger and more severely injured with a higher incidence of head and neck injury (56% vs. 30%, p<0.001). 5 Another article evaluated the differences in injury patterns according to seat position: i) Victims who were front seated passengers had the highest mortality. ii) Rear seat passengers were found to be at greater risk for serious traumatic brain injuries (BTIs).…”
Section: To the Editormentioning
confidence: 99%